Radiation-Induced Transformation of Immunoregulatory Networks in the Tumor Stroma - Martinez-Zubiaurre, Inigo; Chalmers, Anthony J.; Hellevik, Turid (Frontiers in Immunology, 2018)
The implementation of novel cancer immunotherapies in the form of immune-checkpoint blockers is becoming one of the biggest quantum leaps in the history of cancer management, and has renewed the enthusiasm for identifying new ways to induce antitumor immune responses in patients. Despite the probed efficacy of neutralizing antibodies against immune-checkpoints on refractory cancers, many patients do not experience therapeutic benefit, possibly owing to the lack of a pre-existing anti-tumor immune recognition, or to the presence of dominant immunosuppressive mechanisms in the tumor microenvironment (TME). Recent developments in this field is revealing that local radiotherapy (RT), applied to patients in specific forms, can turn tumors into in situ vaccines, and by itself may also help to overcome some of the barriers to tumor specific immune rejection. RT have the potential to ignite tumor immune recognition by generating immunogenic signals and the release of neoantigens, however, the multiple immunosuppressive forces in the TME represent important barriers for successful tumor rejection. In this review, we gather knowledge on the changes in the stromal compartments of tumors induced by local RT that could have an impact on tumor immune attack. Since different RT regimens are known to mediate strikingly different effects on the multifarious elements of the tumor stroma, special emphasis is given to the different RT schemes and the time post treatment when the effects are measured. A better understanding of the TME remodeling following specific RT regimens and the window of opportunity offered by RT will aid to the design of optimal treatment combinations.